The influence of common exercise on the prevalence of hypertension - Ting Liu; Junmin Zhou; Yuezhu Chen; Jie Xu; Shaoxiong Yang; Kangzhuo Baima; Tingting Yang; Jing Zhou (BMC Public Health)
Abstract Background Numerous studies have shown that physical activity can effectively reduce blood pressure. And exercise is a physical activity that we can control, so which kind of exercise modalities is more closely related to the prevalence of hypertension needs further research. Methods This study's data came from the baseline survey of the China Multi-Ethnic Cohort. Sociodemographic information, physical activity, and hypertension prevalence were extracted to analyze the relationship between different common exercise modalities and the prevalence of hypertension. Results A total of 40,308 participants were included, and the prevalence of hypertension was 34.0%.The main exercise modalities of 24,260 (60.2%) respondents were Taichi /Qigong /leisure walking, 9046 (22.4%) brisk walking /gymnastics /folk dancing, 3194 (7.9%) jogging /aerobic exercise, 312 (0.8%) swimming, 1509 (3.7%) ball game, 657 (1.6%) equipment exercise, and 1330 (3.3%) others (e.g. mountain climbing). Compared with walking, jogging /aerobic exercise (OR: 0.781; 95%CI: 0.648–0.942), ball game (OR: 0.685; 95%CI: 0.539–0.871), and others (e.g. mountain climbing) (OR: 0.713; 95%CI: 0.528–0.964) they had a lower prevalence of hypertension. Among males, playing ball games (OR: 0.628; 95%CI: 0.476–0.827) had a lower prevalence of hypertension, while among females it was jogging /aerobic exercise(OR: 0.531; 95%CI: 0.371–0.762). Youth group who took jogging /aerobic exercise (OR: 0.642; 95%CI: 0.436–0.945) and ball game (OR: 0.416; 95%CI: 0.26–0.665) had a lower prevalence of hypertension. Conclusion People who do ball games, jogging /aerobic exercise, and others (e.g. mountain climbing) exercises had a lower prevalence of hypertension than walking, and there were differences between age and sex.